Exploring the necessity of corporate dynamic capability and sustainable performance - Li Mingxing; Ma Zhiqiang; Bailin Ge; Song Xinping; Mohammad Heydari; Maulid H. Bwabo (South African Journal of Economic and Management Sciences)
Background: Many studies navigated corporate dynamic capability’s direct and indirect effects on sustainable performance. However, there is an empirical literature conundrum regarding the sufficient and necessary condition of corporate dynamic capability that can enhance the sustainable performance of microfirms.